CAUSES OF OSTEOPOROSIS, METHODS OF DETECTION, WAYS OF PREVENTION AND TREATMENT. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
this article provides complete information about the currently widespread disease osteoporosis. It also provides recommendations on the causes of this disease and treatment measures.